KEMAMPUAN GURU SOSIOLOGI DALAM MELAKSANAKAN PROSES PEMBELAJARAN DI SMA NEGERI 1 PASAMAN KABUPATEN PASAMAN BARAT - Rahman, Putri Anita; Ansofino, Ansofino; Marleni, Marleni (Pendidikan Sosiologi, 2013)
Â Main problem which is researched in this research is to explain teacherâs ability forward sociology material understanding in adjustment with learning method. In addition the purpose of this research is to know teacherâs ability toward sociology material understanding in adjustment with learning method.Research method that is used in this research is qualitative method especially case study type. Research informant was sociology teacher, headmaster, students of ten, elevent, and twelve class. Technigue of data collection is done by three ways, there are : observation, interview and documentation study. Technigue of data analysis has several ways below: data collection, data reduction, data presentation and conclusion with drawal.Based on the result of the research, it could be concluded that sociology teacherâsability in implementing learning process in SMAN 1 Pasaman, Pasaman Barat regency, involve:Teacherâs ability in sociology material understanding was still not good because the teacher who teach lesson was not teacher who had background sociology discipline. So, the teacher did not understand the material, and teacherâs knowledge about sociology subject was still limited.Teacherâs ability adjusted lesson plan with lesson implementation was not optimal because the teacher did not understand in implementing lesson method, so the method lesson was not effective and variation did run well. It caused the student felt bored in learning proces. And finally students interest to follow sociology lesson was reduced.Teacherâs ability interaction and communication with students in learning proces still had obstacle because the teacher could not create comfortable learning atmosphere which can make students feel interest. So, the efort to create and keep students to think critical and sensitive social tendency around was often pasted.